9x-3(2-x)=4(3x+8)-7x

Simple and best practice solution for 9x-3(2-x)=4(3x+8)-7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-3(2-x)=4(3x+8)-7x equation:


Simplifying
9x + -3(2 + -1x) = 4(3x + 8) + -7x
9x + (2 * -3 + -1x * -3) = 4(3x + 8) + -7x
9x + (-6 + 3x) = 4(3x + 8) + -7x

Reorder the terms:
-6 + 9x + 3x = 4(3x + 8) + -7x

Combine like terms: 9x + 3x = 12x
-6 + 12x = 4(3x + 8) + -7x

Reorder the terms:
-6 + 12x = 4(8 + 3x) + -7x
-6 + 12x = (8 * 4 + 3x * 4) + -7x
-6 + 12x = (32 + 12x) + -7x

Combine like terms: 12x + -7x = 5x
-6 + 12x = 32 + 5x

Solving
-6 + 12x = 32 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-6 + 12x + -5x = 32 + 5x + -5x

Combine like terms: 12x + -5x = 7x
-6 + 7x = 32 + 5x + -5x

Combine like terms: 5x + -5x = 0
-6 + 7x = 32 + 0
-6 + 7x = 32

Add '6' to each side of the equation.
-6 + 6 + 7x = 32 + 6

Combine like terms: -6 + 6 = 0
0 + 7x = 32 + 6
7x = 32 + 6

Combine like terms: 32 + 6 = 38
7x = 38

Divide each side by '7'.
x = 5.428571429

Simplifying
x = 5.428571429

See similar equations:

| x^2=0.11-1.8x | | (6x+11+9x)= | | r+7-1=6 | | 0.7=x-1.2x | | b/5-9=-1 | | 9000=.07*1*x | | 43=-7+5x | | 3ln(3x-4x^3)=0 | | X+2y=195 | | x*y=24 | | 2.8=ln(y) | | 9000=.05*1*x | | 6x-6x+9=9 | | 15=1+6a+a | | 15x+5=135 | | 1+5p+8p=1 | | x+y=39 | | 6r-5r=-7 | | 1x+2y=49 | | -9=c/12 | | 98=6+34 | | 5=7v+8+4 | | Ln(8x+2)=Ln(4x-10) | | 50/5= | | 12x+5x+7=9 | | -6=k-8-1 | | 4(3-5x)=3(-3x+15) | | 4/x=2/11 | | 10x-3=7x-11 | | 10/2= | | 13=-7p-6p | | a^2-9=40 |

Equations solver categories